Are the frictional properties of creeping faults persistent? Evidence from rapid afterslip following the 2011 Tohoku‐oki earthquake. Issue 14 (30th July 2013) - Fukuda, Jun'ichi; Kato, Aitaro; Kato, Naoyuki; Aoki, Yosuke
<x xml:space="preserve">Abstract</x> [1] Geophysical observations and numerical studies have shown that creeping portions of faults have persistent rate‐strengthening frictional properties and can act as barriers to earthquake rupture propagation. On the basis of GPS data following the 2011 MW 9.0 Tohoku‐oki earthquake in Japan, we find that the evolution of afterslip and postseismic shear stress on the plate interface is inconsistent with persistent rate‐strengthening frictional properties but is consistent with slip‐rate‐dependent frictional properties that exhibit less rate‐strengthening with increasing slip rate. Such slip‐rate‐dependent frictional properties tend to prevent creeping regions from acting as barriers to rupture propagation and therefore could be an important factor in determining the spatial extent of individual earthquakes.